2006
DOI: 10.1099/jmm.0.46733-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and virulence markers of Yersinia enterocolitica strains from human, animal and food origins isolated between 1968 and 2000 in Brazil

Abstract: Molecular typing and virulence markers were used to evaluate the genetic profiles and virulence potential of 106 Yersinia enterocolitica strains. Of these strains, 71 were bio-serotype 4/O : 3, isolated from human and animal clinical material, and 35 were of biotype 1A or 2 and of diverse serotypes, isolated from food in Brazil between 1968 and 2000. Drug resistance was also investigated. All the strains were resistant to three or more drugs. The isolates showed a virulence-related phenotype in the aesculin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 53 publications
4
89
1
7
Order By: Relevance
“…Y. enterocolitica has been isolated from raw milk and pasteurized dairy products in several countries e.g. in the USA (Jayarao and Henning, 2001), China (Wang et al, 2010;Ye et al, 2014), Mexico (Bernardino-Varo et al, 2013), Brazil (Falcão et al, 2006), Iran (Soltan-Dallah et al, 2004;Rahimi et al, 2014;Jamali et al, 2015), India (Subha et al, 2009), Turkey (Guven et al, 2010), Nigeria (Okeke and Okwori, 2014), Egypt (Darwish et al, 2015) and other countries. In Algeria, the raw milk is still frequently consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Y. enterocolitica has been isolated from raw milk and pasteurized dairy products in several countries e.g. in the USA (Jayarao and Henning, 2001), China (Wang et al, 2010;Ye et al, 2014), Mexico (Bernardino-Varo et al, 2013), Brazil (Falcão et al, 2006), Iran (Soltan-Dallah et al, 2004;Rahimi et al, 2014;Jamali et al, 2015), India (Subha et al, 2009), Turkey (Guven et al, 2010), Nigeria (Okeke and Okwori, 2014), Egypt (Darwish et al, 2015) and other countries. In Algeria, the raw milk is still frequently consumed.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between autoaggregation and virulence has been shown for many Gram-negative bacteria such as Yersinia enterocolitica (19,38,44), Escherichia coli (67), Campylobacter jejuni (32), and Vibrio cholerae (14). In one study, autoaggregation was observed in about 70% of human and animal clinical isolates of Y. enterocolitica, whereas all environmental isolates tested were negative for autoaggregation (38).…”
mentioning
confidence: 99%
“…In one study, autoaggregation was observed in about 70% of human and animal clinical isolates of Y. enterocolitica, whereas all environmental isolates tested were negative for autoaggregation (38). Thus, the autoaggregation phenotype has been used as a virulence marker for enteropathogenic Yersinia (19,38). Enteropathogenic Yersiniae species, Y. enterocolitica and Y. pseudotuberculosis, autoaggregate via a YadA-mediated hydrophobic interaction in tissue culture medium at 37°C (60).…”
mentioning
confidence: 99%
“…Genomic DNA was extracted from the growing cells as described by Falcão et al (2006). The DNA concentration of each sample was determined using a NanoDrop 1000 (Thermo Scientific, San Jose, CA, USA), and the purity of the DNA was estimated as described by Sambrook and Russell (2001).…”
Section: Dna Extractionmentioning
confidence: 99%